The Association between Body Mass Index and Physical Fitness in Adolescents - Muhammad Eka Mardyansyah Simbolon; Dzihan Khilmi Ayu Firdausi (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
The lifestyle and  dietary habit of the modern society can lead to overweight and obesity. Overweight and obesity are now beginning to worry. This study was aimed at providing a description of the condition of Body Mass Index (BMI) and physical fitness among adolescents in Bangka Belitung Islands in 2017 and how BMI and physical fitness are associated. 105 adolescents were participated in this study, consisting of 90 male and 15 female adolescents. Participants were at age ± 18 years in the year when the study was conducted. Anthropometry test was conducted to identify participants' BMI. Performance tests were conducted to identify the components of health related to physical fitness. The performance test included vertical jump (leg power), sprint 60 meter (speed), push-up (strength and endurance of arm muscle), sit-up (strength and endurance of abdominal muscles), and run / walk for 1000/1200 meters (cardiorespiratory endurance). BMI has a significant correlation with the strength and endurance of arm muscle . BMI has a significant correlation with leg power. BMI correlates significantly with speed. CRE is only significantly correlated with abdominal muscle strength and endurance. Overweight and obesity can be prevented through the provision of a program of physical activity. AbstrakGaya hidup dan pola makan masyarakat modern saat ini dapat menyebabkan kelebihan berat badan dan obesitas. Obesitas dan kelebihan berat badan pada saat ini mulai mengkhawatirkan. Penelitian ini bertujuan untuk memberikan gambaran tentang kondisi Indeks Masa Tubuh (IMT) dan kebugaran jasmani remaja di Kepulauan Bangka Belitung pada tahun 2017 dan bagaimana keterkaitan antara IMT dan kebugaran jamani. Pertisipan pada pnelitian ini adalah 105 remaja yang terdiri dari 90 remaja laki-laki dan 15 remaja perempuan dengan usia rata-ratae ± 18 tahun. Tes antropometri dilakukan untuk mengidentifikasi IMT. Sedangkan tes performa dilakukan  untuk mengidentifikasi komponen-komponen kebugaran jasmani yang terkait dengan kesehatan. Tes performa yang diberikan adalah lompat vertikal (power tungkai), lari cepat 60 meter (kecepatan), push-up (daya tahan kekuatan lengan), sit-up (daya tahan kekuatan otot perut), dan berlari  / berjalan jarak 1000/1200 meter (daya tahan kardiorespirasi). IMT memiliki korelasi yang signifikan dengan daya tahan kekuatan otot lengan. IMT memiliki korelasi yang signifikan dengan power tungkai. IMT berkorelasi secara signifikan dengan kecepatan. CRE hanya berkorelasi signifikan terhadap data tahan kekuatan perut. Kegemukan dan obesitas dapat dicegah melalui pemberian program aktivitas fisik yang tepat.